2012
DOI: 10.1038/npp.2012.168
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Stress Exposure Increases the Excitation of Dopamine Neurons in the Ventral Tegmental Area and Alters Their Reponses to Psychostimulants

Abstract: Prenatal stress exposure (PSE) is known to increase addiction risk. Dopamine (DA) neurons in the ventral tegmental area (VTA) play an important role in addiction. In order to understand the cellular mechanisms underlying PSE-induced increase in addiction risk, we examined the effects of PSE on the electrical impulse activity of VTA DA neurons using the in vivo extracellular single-unit recording technique. Amphetamine self-administration was also conducted to confirm increased addiction risk after PSE. The PSE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Thus, the increased number of c-Fos 1 neurons in ventral motor thalamic nuclei indicates an overflow of the basal ganglia motor programming to the cerebral cortex in PRS rats. This explains the resistance to haloperidol-induced catalepsy and the enhanced motor response to apomorphine we have found in PRS rats, and is in line with the increased motor response of PRS rats to a novel environment and to cocaine or other psychostimulants (Deminière et al, 1992;Henry et al, 1995;Morley-Fletcher et al, 2004;Koenig et al, 2005;Kippin et al, 2008;Thomas et al, 2009;Mairesse et al, 2012;Hausknecht et al, 2013).…”
Section: Discussionsupporting
confidence: 85%
“…Thus, the increased number of c-Fos 1 neurons in ventral motor thalamic nuclei indicates an overflow of the basal ganglia motor programming to the cerebral cortex in PRS rats. This explains the resistance to haloperidol-induced catalepsy and the enhanced motor response to apomorphine we have found in PRS rats, and is in line with the increased motor response of PRS rats to a novel environment and to cocaine or other psychostimulants (Deminière et al, 1992;Henry et al, 1995;Morley-Fletcher et al, 2004;Koenig et al, 2005;Kippin et al, 2008;Thomas et al, 2009;Mairesse et al, 2012;Hausknecht et al, 2013).…”
Section: Discussionsupporting
confidence: 85%
“…(Chocyk et al, 2011b). An increase in behavioral responses to psychostimulants is a common feature of MS animals that has been observed in many studies (Brake et al, 2004; Kikusui et al, 2005; Kosten et al, 2005; Kippin et al, 2008; Chocyk et al, 2011b; Hausknecht et al, 2013). These data correlate with an increased risk for drug abuse and addiction in humans subjected to early‐life adversity (Andersen and Teicher, 2008, 2009; Green et al, 2010; Kessler et al, 2010).…”
Section: Discussionmentioning
confidence: 83%
“…To investigate the effects of ELS on brain development and maturation, several animal models have been developed, including (1) prenatal stress (Kippin et al, 2008;Hausknecht et al, 2013), (2) perinatal glucocorticoid (GC) exposure (McArthur et al, 2007;Virdee et al, 2014), and (3) maternal (or parental) separation (Brake et al, 2004;Chocyk et al, 2010Chocyk et al, , 2011aBraun et al, 2013). Behavioral and biochemical data have strongly indicated that animals subjected to ELS procedures display sex-dependent functional changes in the dopaminergic system (Hall et al, 1999;Kosten et al, 2005;Chocyk et al, 2011b;Kunzler et al, 2015;Virdee et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Levels of estrogen receptors within the MPOA are masculinized within the brain of prenatally stressed females (i.e., increased in stressed females) as are circulating levels of estrogen, which are decreased in prenatally stressed females (Del Cerro, Ortega, Gomez, Segovia, & Perez‐Laso, ). Prenatal stress alters the activity of midbrain DA neurons (Hausknecht, Haj‐Dahmane, & Shen, ; Kaiser, Kruijver, Swaab, & Sachser, ), increases levels of the DA transporter within striatal regions (Converse et al., ), and increases DA release in the nucleus accumbens (Alonso, Navarro, Santana, & Rodriguez, ). These outcomes in adulthood may be a consequence of prenatal stress‐induced alterations in the developmental expression of transcription factors involved in DA neuron differentiation and survival, namely Nurr1 and Pitx3 (Baier, Katunar, Adrover, Pallares, & Antonelli, ; Sousa et al., ; Volpicelli et al., ).…”
Section: Prenatal Influence On the Maternal Brainmentioning
confidence: 99%